SOME ASPECTS OF INCREASING THE EFFECTIVENESS OF PHARMACOTHERAPY FOR ACUTE PNEUMONIA IN YOUNG CHILDREN - Fatima F. Xoltayeva (Scholar Express Journals, 2023)
Endogenous intoxication syndrome (EIS) continues to be one of the most pressing problems in pediatrics to this day. About 90% of all pathological conditions in pediatrics occur against the background of endogenous intoxication
Keywords: Endogenous intoxication; pneumonia in children; effectiveness of drugs